Simultaneous Estimation of Admixture drugs by RP-HPLC: A Review - Saini, Shipra; Mandal, Sulekha; Agarwal, Dilip (Asian Journal of Pharmaceutical Research and Development, 2020)
Recently, high demand of high-throughput analyses with high sensitivity and selectivity to molecules and drugs in different classes with different physical-chemical properties and a reduction in analysis time—is a principal milestone for novel methodologies that researchers are trying to achieve especially when analytical procedures are applied to clinical purposes. In addition, to avoid high doses of a single drug that could cause serious side effects, multi-drug therapies are often used to treat numerous diseases. For these reasons, the demand for methods that allow the rapid analysis of mixed compounds has increased in recent years. In order to respond to these needs, new methods and instruments have been developed. However, often the complexity of a matrix can require a long time for the preparation and processing of the samples. Different problems in terms of components, types of matrices, compounds and physical-chemical complexity are encountered when considering drugs association profiles for quantitative analyses. This review addresses not only recently optimized procedures such as chromatographic separation, but also methods that have allowed us to obtain accuracy (precision and trueness), sensitivity and selectivity in quantitative analyses for cases of drug associations.